MONITORING OF RIVERBANKS AS A PART OF STATE MONITORING OF WATER BODIES: CURRENT STATE AND DEVELOPMENT PROSPECTS - Danila I. Shkolnyi; Aleksandr S. Zavadskiy (Водное хозяйство России: проблемы, технологии, управление)
In the last decade, a program of state monitoring of water bodies has been implemented in Russia, aimed at collecting and summarizing relevant information on the state of rivers, lakes, and reservoirs. The data obtained during its implementation is entered into a unified automated information system for state monitoring of water bodies – AIS GMVO (automated information system of state water bodies monitoring), available to any user in the format of a web directory. The main body of information presented in the AIS GMVO is the materials of observations of the hydrological, hydro/chemical and hydro/biological characteristics of water bodies obtained at stations and gauges subordinate to the Federal Service for Hydrometeorology and Environmental Monitoring (Roshydromet) and individual executive bodies of the constituent entities of the Russian Federation. An important block in them is represented by the results of stationary observations of the variability and state of the river banks within the water protection zones. In the case of further development of the monitoring network, methodological improvement and unification of the observation program, the analysis of the obtained data will gain great scientific and practical importance, allowing to significantly expand the understanding of regional features and spatio-temporal variability of channel processes in Russia. The purpose of this work is to analyze the current state of the riverbanks monitoring system based on more than 10 years of data accumulation, as well as to assess the available results of its implementation.